A Comparison of Entomopathogenic Nematode Longevity in Soil under Laboratory Conditions - Shapiro-Ilan, David I. (The Society of Nematologists, 2006)
We compared the longevity of 29 strains representing 11 entomopathogenic nematode species in soil over 42 to 56 d. A series of five laboratory experiments were conducted with six to eight nematode strains in each and one or more nematode strains in common, so that qualitative comparisons could be made across experiments. Nematodes included Heterorhabditis bacteriophora (four strains), H. indica (Homl), H. marelatus (Point Reyes), H megidis (UK211), H. mexicana (MX4), Steinernema carpocapsae (eight strains), S. diaprepesi, S. feltiae (SN), S. glaseri (NJ43), S. rarum (17C&E), and S. riobrave (nine strains). Substantial within-species variation in longevity was observed in S. carpocapsae, with the Sal strain exhibiting the greatest survival. The Sal strain was used as a standard in all inter-species comparisons. In contrast, little intra-species variation was observed in S. riobrave. Overall, we estimated S. carpocapsae (Sal) and S. diaprepesi to have the highest survival capability. A second level of longevity was observed in H. bacteriophora (Lewiston), H. megidis, S. feltiae, and S. riobrave (3–3 and 355). Lower levels of survivability were observed in other H. bacteriophora strains (Hb, HP88, and Oswego), as well as S. glaseri and S. rarum. Relative to S. glaseri and S. rarum, a lower tier of longevity was observed in H. indica and H. marelatus, and in H. mexicana, respectively. Although nematode persistence can vary under differing soil biotic and abiotic conditions, baseline data on longevity such as those reported herein may be helpful when choosing the best match for a particular target pest.